Prospective 2-year biomechanical analysis during rehabilitation of a severe knee injury in an elite gymnast: a case study - Cottam, D.; Hunter, A.; Perera, N.; Rigg, J. (Journal of Science and Medicine in Sport, 2021)
Introduction: Anterior cruciate ligament (ACL) injuries are one of the most common and debilitating sports injuries. Strength deficits due to neuromuscular impairments are common following ACL injuries and may lead to functional deficits. Regaining of symmetrical movement following ACL injury can take longer than 9 months and may have implications for athlete rehabilitation, return to performance and risk of subsequent injury. In this case report we present biomechanical analysis of various functional movements of a 24-year-old elite gymnast who sustained an ACL rupture, extensive lateral meniscus tear and lateral femoral condyle (LFC) impaction fracture during a competition and attended AIS Intensive Rehabilitation (AISIR), a multi-disciplinary rehabilitation program. Methods: The athlete began the AISIR program 2-weeks post-injury, and at 6-weeks post-injury he underwent an ACL reconstruction, lateral meniscectomy and LFC chondroplasty. Biomechanical testing was performed at 3-, 6-, 9-, 17- and 21-months post-injury using force plate analysis, high speed cameras and VICON motion capture cameras. Initial simple movement analysis (e.g. walking, submaximal running) progressed to complex skills (e.g. landings from height, repeated hop for distance) later in the rehabilitation. Ground reaction forces, joint angles, and joint moments around multiple axes for both legs were analyzed with statistical parametric mapping (SPM) and used by the AISIR team to inform the rehabilitation plan and skill progression. Results: The rehabilitation process was uncomplicated except for a 2-month venue shutdown due to the SARS-CoV-2 pandemic. The athlete exhibited statistically significant (p<0.05) between-leg asymmetries through the walking gait cycle in both joint kinetics and kinematics of the lower limb early in rehabilitation. The ankle plantarflexion/extension was asymmetrical through 89% of stride (p<0.05), with peak right ankle dorsiflexion 18.6+/-1.4° vs left 15.5+/-2.7° during stance. Asymmetries of pelvic rotation during walking persisted until the 21-month analysis. Some between leg asymmetries continued up to the 21-month analysis of more complex skills (e.g. maximal sprinting braking ground reaction force asymmetry through 86% of stance, peak braking force 244.2+/-56.8N on right vs 343.4+/-79.5N on left), though the athlete had returned to unrestricted training and performed symmetrically on a battery of hopping, strength and functional tests at this time. Discussion: Similar to existing evidence, we found that return to symmetrical performance of functional movements takes longer than 9- to 12-months, which is often taken to return an ACL-injured athlete to training and competition. Returning to knee-strenuous sporting activities before achieving symmetrical knee function may increase the risk of subsequent injury.